Preservation of the environment through sustainable agriculture practices: a case study on the attitude of crop farmers - D’Silva, Jeffrey Lawrence; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Man, Norsida (Science Publications, 2011)
Problem statement: Undoubtedly agriculture over the years has been a remarkable source of income generator for the rural community to achieve a higher standard of living and to live on par with their urban brethren that are mostly involved in industrialization. The quest for a greater income should, however, not deter farmers from paying attention toward the preservation of the environment in terms of protecting the quality of land, air and water so that our present and future generation will be able to have sufficient resources for their survival. Thus, having a positive attitude toward practicing the elements of sustainable agriculture without doubt will help farmers to emphasize on the need to protect the environment. As such, this study is designed to understand contract farming entrepreneurs’ attitude toward the preservation of the environment through sustainable agriculture practices and the issues involved in determining their level of attitude. Approach: The study employed qualitative methodology in the form of a focus group discussion and the data was collected from seven contract farming entrepreneurs in Cameron Highlands, Malaysia. In the data collection process, the researcher played the role as the instrument and an interview guide that was developed prior to it enabled the researcher to achieve the objectives of the study. A couple of voice-recorders assisted in recording the discussion and it was later transformed into verbatim transcripts for data analysis. Results: The outcome of the study showed that in general, crop farmers face an upheaval task in possessing a positive attitude toward practicing sustainable agriculture in spite of having a sound knowledge about it. They perceive that much support is needed from the respective stakeholders that would enable them to embrace sustainable agriculture practices. Conclusion/recommendations: It is recommended that various stakeholders could play more important roles such as providing trainings to farmers and having a tighter control on prices of crops that will enable farmers to hold a positive attitude on sustainable agriculture practices.